Biosorptive Removal of Malachite Green, Methylene Blue and Methyl Orange Dyes from Aqueous Solutions by Ficus bengalensis (Banyan) Tree Leaves - Aslam Malana, Muhammad; Amanat, Tahira; Beenish Qureshi, Raheela; Badaruddin Ahmad, Hafiz (Asian Journal of Chemistry, 2012)
Biosorption studies of malachite green, methylene blue and methyl orange dyes were carried out on Banyan tree leaves at 298 K and 308 K. The equilibrium data for the adsorption of all the dyes were well described by Freundlich isotherm at both the temperatures. The adsorption of these dyes on the adsorbent follows pseudo second order kinetics with film diffusion and pore diffusion to be the rate limiting steps. Thermodynamic studies of the adsorption process revealed adsorption of malachite green and methylene blue to be spontaneous whereas that of methyl orange to be non-spontaneous. The value of adsorption capacity (qm) calculated for the adsorption of malachite green, methylene blue and methyl orange at 308 K are 17.76, 12.57 and 2.56 mg/g, respectively. Keeping in view the higher values of (qm) for malachite green and methylene blue, it is suggested that Banyan tree leaves can be effectively used for the removal of these dyes.